Student Dropout at a Newly Established University - Emmanuel L. Howe; Lukas Kahare (Universal Journal of Educational Research, 2025)
In higher education the phenomenon of student dropout is defined as a departure of a student from a programme before obtaining an academic qualification. To address this situation many universities worldwide had developed and adopted various strategies to remedy the situation, however the challenge persist per year. This study adopted a qualitative approach, and the aim was to explore the reasons why students at Botho University dropout as well as the factors that affect student within the context of higher education landscape. who had previously enrolled at Botho University Eswatini were interviewed to gather the reasons as well as the perception of how dropping out of the university could have been avoided. Purposive and snowball sampling was used in this study. The findings show that although some of the students were awarded scholarships, the dropout cases persisted, which greatly affected their attempts to return for the following semester. The overall determining factor is that both parents and students had a perception that the scholarships will cover every aspect of the academic life of the student. Recommendations include a more comprehensive and detailed analysis of student readiness particularly in the financial aspect, constant involvement of parents regarding financial affordance and financial tracking systems to alert the university for prompt intervention.